The location of constitutional neurofibromatosis 2 (NF2) splice site mutations is associated with the severity of NF2. Issue 7 (1st July 2005) - Baser, M E; Kuramoto, L; Woods, R; Joe, H; Friedman, J M; Wallace, A J; Ramsden, R T; Olschwang, S; Bijlsma, E; Kalamarides, M; Papi, L; Kato, R; et al.
Abstract : Neurofibromatosis 2 (NF2) patients with constitutional splice site NF2 mutations have greater variability in disease severity than NF2 patients with other types of mutations; the cause of this variability is unknown. We evaluated genotype-phenotype correlations, with particular focus on the location of splice site mutations, using mutation and clinical information on 831 patients from 528 NF2 families with identified constitutional NF2 mutations. The clinical characteristics examined were age at onset of symptoms of NF2 and number of intracranial meningiomas, which are the primary indices of the severity of NF2. Two regression models were used to analyse genotype-phenotype correlations. People with splice site mutations in exons 1–5 had more severe disease than those with splice site mutations in exons 11–15. This result is compatible with studies showing that exons 2 and 3 are required for self-association of the amino terminal of the NF2 protein in vitro, and that deletions of exons 2 and 3 in transgenic and knockout mouse models of NF2 cause a high prevalence of Schwann cell derived tumours.